55 Gene-gene interactions in coronary artery disease. (9th June 2011) - Musameh, M D; Wang, W Y S; Balmforth, A J; Ball, S G; Hall, A S; Tomaszewski, M; Samani, N J
Abstract : Background: Only a small fraction of the heritability of coronary artery disease (CAD) has been explained by common variants identified by genome-wide association studies. Among the stones to be turned in the hunt for the missing heritability of CAD are gene-gene interactions. We investigated whether interactions between common alleles in genes and pathways of known importance to cardiovascular regulation may contribute to the heritability of CAD. Methods: 2101 CAD cases and 2426 controls of Caucasian origin recruited into Wellcome Trust Case Control Consortium were genotyped using 50 K IBC gene-centric array containing 45 707 single nucleotide polymorphisms (SNPs) of the highest biological relevance to cardiovascular system. After applying appropriate quality control filters, 11 332 common (minor allele frequency >10%), independent (r 2 linkage disequilibrium coefficient of ≤0.5) were included in pair-wise SNP-SNP interaction analysis using two complementary statistical approaches: logistic regression (PLINK and INTERSNP software packages) and Bayesian model (BEAM software). Results: None of the analysed SNP-SNP interactions was statistically significant after correction for multiple testing (p=7.8×10 -10 ). The most significant interaction identified in this analysis was between rs727139 (KCNH8) on chromosome 3 and rs11167496 (PDGFRB) on chromosome 5 (p=2.45×10 −8 ). Analysis of subsets of SNPs pre-selected based on their nominal association with CAD (p<0.05) or molecular functionality (non-synonymous SNPs) did not contribute more significant findings than investigation of random set of SNPs. Conclusion: Our analysis suggests that common SNP-SNP interactions are unlikely to account for a large proportion of the missing heritability of CAD.